THE INFLUENCE OF CAPITAL EFFICIENCY AND EDUCATION SPENDING ON INDONESIA’S ECONOMIC GROWTH - Innes Clara Shinta; Akhmad Solikin (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The efficiency of translating capital toward economic growth has been contested in Indonesia, especially when the economic policies could not achieve economic growth targets. In addition, budget allocation for education sector as a human capital investment is substantial and needs to be assessed its the impact on the economic growth. This research examines relationship between capital efficiency measured by the incremental capital output ratio (ICOR) and education spending on economic growth using 2015 to 2019 data for 34 provinces in Indonesia. Analyses were performed using Pearson correlation and panel data regression. The results show that ICOR has a negative correlation with economic growth for majority of provinces. Regression results show that ICOR negatively affects economic growth, while education spending positively affects economic growth, as expected by theory. The results suggest that the government policy to induce economic growth can be achieved by reducing the value of ICOR as well as to allocate the education spending.